METHOD OF CALCULATION OF PROTECTION OF PERSONAL DATA FROM EXPANSION OF SOCIAL NETWORKS - Akhramovych, Vladymyr; Lazarenko, Sergey; Nimchenko, Tetiana; Ryabova, Lyubov (Science-based technologies, 2022)
Calculating or estimation of the size of network expansion can give an idea of the impact of the spread of unauthorized information by malicious users. Once a malicious node is added to your contact list, it can access sensitive data and disclose it indiscriminately using social media tools such as placing ad boards, publishing images, etc. Such an impact can be measured by calculating the average ratio of friends, which can get confidential information disclosed by an intruder. The completed study of the linear model of protection against network expansion allowed to obtain a system of linear equations of information protection in social networks (SN) depending on the type and parameters of network expansion. The conditions of the system stationary position were found, the system of equations by the method of "small deviations" was solved, graphical dependencies were obtained, and the fluctuations of the protection system were iteration. The use of the method of differentiation of the protection function allowed to investigate the behavior of the system. The equation of information protection is an equation of a harmonic oscillator with a suffocation amplitude and breaks down into three cases: pre-resonant zone, resonant and after resonance. Obtained own and forced frequencies of oscillations of the system, period of oscillations, attenuation factor. In the pre-resonance zone, the oscillation zone of the protection system is linear (except for the transition process), the protection indicator is the largest, in the resonance zone of the oscillation of the protection system is nonlinear, there is no protection, there is no protection in the resonant zone, the fluctuations in the protection system are nonlinear, the protection is minimal.